Model Kepemimpinan Transformasional Pada Pemimpin Perempuan: Studi Kasus Pemberdayaan Perempuan - Auladina, Adinda Maula; Asy’ari, Hasyim (Innovative: Journal Of Social Science Research, 2025)
This study aims to determine the concept of transformational leadership, understand women's leadership, and identify the influence of women's leadership on the concept of transformational leadership. The research method used by the author uses qualitative research using a descriptive method where writing must be able to describe data and facts that occur in the field to obtain accurate research results. This study concludes that women have the same rights as men as leaders. Women are no longer seen as meek creatures. Instead, they play an important role in family life, companies, and society. Along with reforms and gender concepts, women are positioned fairly in all areas of life, including in leadership roles. Gender issues show that there is no gender discrimination in organizations. However, when gender is associated with leadership style, there is a certain leadership style that women have. Not because of gender differences, but more because of characteristics related to work. In terms of these job characteristics, it was found that women's leadership is divided into two types: feminism and transformational.